Good Corporate Governance dalam Perspektif Konvensional Dan Islam (Studi Deskriptif Perbankkan Syariah) - Khoirun Nisa'; Ummu Hani; Mohamad Djasuli (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
This study aims to determine the implementation of Good Corporate Governance from Conventional and Islamic Perspectives. The researcher uses a qualitative descriptive method to analyze the situation with the phenomenon of the object to be studied as the main instrument and focuses more on interpretation than generalization. This research was conducted in the banking sector around the Jombang area. Good corporate governance is the basis for managing and controlling company activities. Although the concept of corporate governance is still new, it is rooted in Islamic teachings such as the Al-Qur'an and Hadith. Therefore, in the framework of implementing the principles of good corporate governance (Good Corporate Governance) in sharia banking, it is appropriate to refer to the existing positive legal provisions, which in turn must apply sharia principles.